Neural Progenitor Cells Expressing Herpes Simplex Virus-Thymidine Kinase for Ablation Have Differential Chemosensitivity to Brivudine and Ganciclovir - Lou, Zijian; Post, Alexander; Rodgers, Christopher E.; Chamankhah, Mahmood; Hong, James; Ahuja, Christopher S.; Khazaei, Mohamad; Fehlings, Michael G. (Frontiers in Cellular Neuroscience, 2021)
Neural progenitor cell (NPC) transplants are a promising therapy for treating spinal cord injury (SCI), however, their long-term role after engraftment and the relative contribution to ongoing functional recovery remains a key knowledge gap. Selective human cell ablation techniques, currently being developed to improve the safety of progenitor cell transplant therapies in patients, may also be used as tools to probe the regenerative effects attributable to individual grafted cell populations. The Herpes Simplex Virus Thymidine Kinase (HSV-TK) and ganciclovir (GCV) system has been extensively studied in the context of SCI and broader CNS disease. However, the efficacy of brivudine (BVDU), another HSV-TK prodrug with potentially reduced bystander cytotoxic effects and in vivo toxicity, has yet to be investigated for NPC ablation. In this study, we demonstrate successful generation and in vitro ablation of HSV-TK-expressing human iPSC-derived NPCs with a >80% reduction in survival over controls. We validated an HSV-TK and GCV/BVDU synergistic system with iPSC-NPCs using an efficient gene-transfer method and in vivo ablation in a translationally relevant model of SCI. Our findings demonstrate enhanced ablation efficiency and reduced bystander effects when targeting all rapidly dividing cells with combinatorial GCV and BVDU treatment. However, for use in loss of function studies for a single cell subpopulation, BVDU alone is optimal due to reduced nonselective cell ablation.